2020
DOI: 10.1108/bjm-07-2019-0254
|View full text |Cite
|
Sign up to set email alerts
|

Fostering intrapreneurial behavior through human resource management system

Abstract: PurposeThis work aims to analyze the effect of employees' perceptions of high-performance work systems (HPWS) on intrapreneurial behavior (IPB), and the potential role of knowledge sharing as a mediating variable in this relationship.Design/methodology/approachHypothesis testing was performed using a structural equation model (SEM) based on a PLS-SEM approach applied to a sample of 297 knowledge-intensive employees from six industrial companies of the Valencian region (Spain).FindingsResults confirmed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 96 publications
1
18
0
1
Order By: Relevance
“…Corporate entrepreneurship is a tool for business development, revenue growth and profitability enhancement (Davidsson, 2015). The pursuit of corporate entrepreneurship is driven by various challenges, including global competition, interest in organizational efficiency for greater profitability, dramatic changes in the marketplace and the perceived limitations in the traditional methods of corporate management (Escribá-Carda et al , 2020). Gallouj (2017) draws an important distinction between conservative and entrepreneurial firms based upon their levels of (a) propensity to innovation and (b) risk-taking behavior.…”
Section: Theory Development and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Corporate entrepreneurship is a tool for business development, revenue growth and profitability enhancement (Davidsson, 2015). The pursuit of corporate entrepreneurship is driven by various challenges, including global competition, interest in organizational efficiency for greater profitability, dramatic changes in the marketplace and the perceived limitations in the traditional methods of corporate management (Escribá-Carda et al , 2020). Gallouj (2017) draws an important distinction between conservative and entrepreneurial firms based upon their levels of (a) propensity to innovation and (b) risk-taking behavior.…”
Section: Theory Development and Hypothesesmentioning
confidence: 99%
“…Tajeddini (2016) has pointed out that opportunity-seeking activities compete for limited capabilities and resources to explore new markets. The recognition of new opportunities relies on such capabilities as information, entrepreneurial experiences and market recognition (Escribá-Carda et al , 2020). These capabilities should also be developed or acquired to balance the exploration and exploitation of opportunities (Barreto and Patient, 2013).…”
Section: Theory Development and Hypothesesmentioning
confidence: 99%
“…Entrepreneurial actions within the context of organizations can be investigated at the organizational level, referred to as corporate entrepreneurship (CE) or at the individual level, conceptualized as intrapreneurship behavior (IPB). Recent advances in the topic favor the examination of IPB because of the scarcity of relevant research and the growing importance of individual human capital in corporate success (Baggen et al, 2016;Escribá-Carda et al, 2020). Intrapreneurial activities have been confirmed to exert positive impacts on various facets of organizational performance such as innovation performance (Ekingen, Ekemen, Yildiz, Korkmazer, 2018), growth and improvement of firms (Augusto Felício et al, 2012), and financial performance (Fis, Cetindamar, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there is emerging interests in examining the impact of human resource (HR) practices on IPB. IPB has been found to be predicted by individual HR practices (Ziyae, 2016;Kühn, Eymann, Urbach, Schweizer, 2016), as well as by a set of interrelated HR applications such as high performance work system (HPWS) (Mustafa, Lundmark, Ramos, 2016;Escribá-Carda et al, 2020). It was found that HPWS influences IPB by enhancing the knowledge and skills necessary for innovative behaviors, providing opportunity for participation in decision making and knowledge sharing, and reciprocating extra-role efforts with appropriate rewards and benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation